Pengaruh Struktur Pembiayaan terhadap Risiko Utang UMKM Perikanan di Kabupaten Buton Selatan - Ahmad Daholu; Ismail Failu; Deki Pardana; Fariz Mustaqim (Jurnal Ragam Pengabdian, 2026)
This study analyzes the effect of financing structure on debt risk among fishery MSMEs in South Buton Regency, Indonesia. Using a mixed-methods approach with a survey of 200 MSMEs, this research developed a Financial Structure Index (FSI) and applied Structural Equation Modeling (SEM). The results show that 66.5% of MSMEs rely on informal financing (pengambe) with an effective interest rate of 238.94% per year. The proportion of informal financing has a positive and significant effect on the probability of default (beta=0.0067; p<0.001) and financial distress index (beta=0.440; p<0.001). MSMEs with a hybrid structure exhibit significantly lower default risk (0.205 vs 0.392; p<0.001) and lower weighted cost of capital (153.39 vs 199.45; p<0.001) compared to informal-dominant MSMEs. These findings underscore the urgency of policy interventions through a blended financing framework that integrates formal credit access, financial literacy, and risk-sharing mechanisms.